Communicative Tasks as a Means of Developing the Emotional Intelligence of Students - Semenog, Olena; Семеног, Олена; Hrona, Nataliia; Грона, Наталія; Khomych, Tetiana; Хомич, Тетяна; Stasiuk, Tetyana; Стасюк, Тетяна Валеріївна; Yurchenko, Artem; Юрченко, Артем; Semenikhina, Olena; Семеніхіна, Олена (MECS,Modern Education & Computer Science Press, 2024)
Emotional intelligence (EI), the ability to manage emotions, empathize, and regulate one's behavior, is essential for every member of society nowadays. Various social institutions, including these at the educational institutions, influence its development. The paper examines the relationship between solving communicative tasks and developing students' emotional intelligence and describes the features of students' native language training. Here, we are providing examples of analytical, associative, and research communicative tasks. The tasks involve communicative activities, emotional and sensory perception of the text, and the involvement of analytical and creative abilities. A pedagogical experiment was conducted to confirm the development of EI in the process of solving communicative tasks. Hall's methodology determined the level of EI formation. The total number of respondents was 156 (control group – people, experimental group – 79 people). Three control surveys were conducted in March (at the beginning of the experiment), June (in the middle of the experiment), and December (at the end of the experiment) of 2022 to track changes in the development of EI. The empirical results were subjected to statistical analysis. Pearson's criterion confirmed the normality of the distributions, and Student's criterion showed the statistical significance of changes at the end of the experiment for all indicators and for the indicators "emotional awareness," "managing one's emotions," and "empathy" in the middle of the experiment. Емоційний інтелект (ЕІ), здатність керувати емоціями, співпереживати та регулювати свою поведінку, є важливою для кожного члена сучасного суспільства. Різні соціальні інститути, зокрема й у навчальних закладах, впливають на його розвиток. У статті розглядається зв'язок між вирішенням комунікативних завдань та розвитком емоційного інтелекту студентів, а також описуються особливості навчання студентів рідній мові. Тут ми наводимо приклади аналітичних, асоціативних та дослідницьких комунікативних завдань. Завдання передбачають комунікативну діяльність, емоційне та сенсорне сприйняття тексту, а також залучення аналітичних та творчих здібностей. Для підтвердження розвитку ЕІ в процесі вирішення комунікативних завдань було проведено педагогічний експеримент. Методологія Холла визначала рівень сформованості ЕІ. Загальна кількість респондентів становила 156 осіб (контрольна група – особи, експериментальна група – 79 осіб). Для відстеження змін у розвитку ШІ було проведено три контрольні опитування у березні (на початку експерименту), червні (в середині експерименту) та грудні (в кінці експерименту) 2022 року. Емпіричні результати були піддані статистичному аналізу. Критерій Пірсона підтвердив нормальність розподілів, а критерій Студента показав статистичну значущість змін наприкінці експерименту для всіх показників та для показників «емоційна усвідомленість», «управління своїми емоціями» та «емпатія» в середині експерименту.
Комунікативні завдання як засіб розвитку емоційного інтелекту студентів
Keywords: emotional intelligence; емоційний інтелект; communicative tasks; комунікативні завдання; communicative approach; комунікативний підхід; professional training; професійна підготовка; teacher training; підготовка вчителів; educational process; освітній процес